Daur al-Lughah al-‘Arabiyyah fi Da’mi Tahrir Palestine wa al-Masjid al-Aqsha - Ningsih, Wiwik Prasetiyo (Dzil Majaz: Journal of Arabic Literature, 2025)
The study of the role of the Arabic language in the liberation of the Palestinian people and Al-Aqsa Mosque is crucial for deeper exploration. This paper seeks to understand three aspects: First, it aims to explore how Arabic, as a mother tongue and religious language, influences the worldview and collective identity of the Palestinian people in their struggle. Second, it focuses on various forms of expression where Arabic is used to voice support for Palestine and Al-Aqsa Mosque. Third, it aims to analyze how Arabic is utilized in education and activism, impacting international understanding and awareness of the Palestinian struggle. This research adopts a qualitative approach with a literature review method. Data collection uses documentary techniques and is analyzed using Content Analysis. The findings reveal three key points: First, through the use of Arabic in education, media, and daily communication, Palestinians internalize their struggle’s narrative. Arabic functions not only as a communication tool but also as a symbol of identity that strengthens the collective determination for freedom. Second, cultural and communicative expressions using Arabic in supporting Palestine's liberation and the protection of Al-Aqsa Mosque are highly diverse, including poetry and literature, social media, sermons and lectures, songs, and music. Third, activism using Arabic to disseminate information through international media, seminars, and conferences plays a significant role in raising global awareness. By utilizing Arabic, activists can reach broader audiences and share stories and perspectives often overlooked by mainstream media. Additionally, collaboration with international organizations based in Arabic-speaking countries helps to spread information about the Palestinian struggle more effectively. Thus, the use of Arabic in education and activism contributes to enhancing global awareness and support for issues faced by the Palestinian people